A comparison of an anterior jaw lift manoeuvre with the Berman airway for assisting fibreoptic orotracheal intubation. - Iqbal, R; Gardner-Thorpe, C; Thompson, J; Popat, M; Yentis, S; Pandit, J (2006)
This study compared the efficacy of an anterior jaw lift manoeuvre with that of the Berman airway in clearing the upper airway during oral fibreoptic tracheal intubation in anaesthetised, paralysed patients. Fifty patients were randomly assigned to undergo fibreoptic-assisted intubation with one method, followed by crossover to the alternative method. The time taken to view the vocal cords was the primary endpoint, and we also noted the rate of failure to view the cords, i.e. cords not seen after 120 s of endoscopy. Anterior jaw lift yielded significantly shorter times to view the vocal cords (median [interquartile range; range]: 22 [17-46; 7-120] s vs 40 [29-67; 21-120] s, p = 0.001) and a higher success rate (49/50 vs 42/50, p = 0.014). We conclude that the anterior jaw lift is more effective than the Berman device for achieving airway clearance in this setting.